First approach to the trophic ecology and diet of the rainbow runner, elagatis bipinnulata (quoy and amp; gaimard, 1825) (pisces: carangidae), in the central colombian caribbean (2014)
The rainbow runner (Elagatis bipinnulata) scores high in trophic level (4.24) but it is not a voracious fish (Q/B = 10.8). Its diet is dominated by the dwarf herring (Jenkinsia lamprotaenia), eats more in the dry season, than in the rainy season and significantly more in the afternoon that in the morning suggesting preference for daylight feeding. Primera aproximación a la ecología trófica del salmón, Elagatis bipinnulata (Quoy y Gaimard, 1825) (Pisces: Carangidae), en el Caribe central colombianoEl salmón (Elagatis bipinnulata) marca alto en nivel trófico (4,24) pero no es un pez voraz (Q/B = 10,8). Su dieta está dominada por la sardina enana (Jenkinsia lamprotaenia), come más en la época seca que en la época de lluvia y come significativamente más en la tarde que en la mañana, lo cual sugiere preferencia por la alimentación diurna.